Detection of heparin by fluorescent sensor based on naphthalimide derivatives in human serum. (October 2020) - Zheng, Junying; Cao, Jian; Tu, Yajing; Wang, Shuxin
Abstract: In the present strategy, a novel sensor Z2 of naphthalimide derivative was designed, synthesized and used to detect the sensitivity and selection of heparin. Z2 was suitable to detect heparin without obvious interference from counter ions and biomolecules in a wide pH range of 3–10. The mechanism of heparin detected by fluorescent sensor was due to the energy change of molecular from the structure rotation of the sensor. A limit of detection of Z2 sensing heparin was 7.56 ng/mL. Z2 can be used to detect heparin in 0.02% human serum sample. Graphical abstract: Image 1 Highlights: The fluorescent intensity of Z2 with heparin at 525 nm was a linear range of 0-15 μg/mL, and LOD reached 7.56 ng/mL. Z2 has high selectivity special against chondroitin sulfate (Chs) and hyaluronic acid (HA). Z2 can be used to detect heparin in 0.02% human serum sample with the recovery from 102.8% to 108.7%.